2019
DOI: 10.1093/mnras/stz2110
|View full text |Cite
|
Sign up to set email alerts
|

Ploonets: formation, evolution, and detectability of tidally detached exomoons

Abstract: Close-in giant planets represent the most significant evidence of planetary migration. If large exomoons form around migrating giant planets which are more stable (e.g. those in the Solar System), what happens to these moons after migration is still under intense research. This paper explores the scenario where large regular exomoons escape after tidal-interchange of angular momentum with its parent planet, becoming small planets by themselves. We name this hypothetical type of object a ploonet. By performing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Our results are in line with those of Sucerquia et al (2019), too, who concluded that long-period planets are more favorable moon hosts than short-period ones. They used a very similar calculation method with the aim of estimating the TTV and TDV signals for detection.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with those of Sucerquia et al (2019), too, who concluded that long-period planets are more favorable moon hosts than short-period ones. They used a very similar calculation method with the aim of estimating the TTV and TDV signals for detection.…”
Section: Discussionsupporting
confidence: 93%
“…However, the synthetic population of moons explored in this work has shown that few of them are within the sensitivity limit of Kepler and TESS (see Figs 7 and 8). Notwithstanding that the detection probability of these moons is low owing to their small size and short a stop , all of them would be detectable with Kepler if we use Transit Timing Variation (TTV) signals, but their existence has to be confirmed with other methods since TTVs can also arise due to interactions with other planets in the system (even with previously detached exomoons or ploonets; Sucerquia et al 2019).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In Fig. 3 we show the fraction of exomoons (n) attached (surviving tidal migration) and detached (mostly ploonets; Sucerquia et al 2019) from its host planet after 4.5 Gyr evolution, respect to the total number of moons (n total ) and as a function of planetary semi-major axis. It can be seen that the chance for a satellite to survive increases with a p .…”
Section: Synthetic Population Of Exomoonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zuluaga et al 2015 and references therein). Also, the magnitude and detectability of TTV and TDV signals for different theoretical populations of exomoons have been constrained (Sucerquia et al 2019(Sucerquia et al , 2020a and delimited in terms of the semi-major axes and masses of systems of moons, indicating that any TTVs or TDVs larger than these constrained values must have a different origin.…”
Section: Introductionmentioning
confidence: 99%